Measuring impacts and financing infrastructure in Kazakhstan - Bibigul Aidarkhanova (Asian Development Bank Institute (ADBI), 2020)
This paper studies the impacts of the infrastructure project on economic development in Kazakhstan. We first overview the macroeconomic situation and the development of public-private partnerships in Kazakhstan. In the empirical part of this research, we use the "difference-in-difference" (DiD) approach to assess the economic impact of the "Khorgos-Zhetygen" railway construction. We further distinguish between effects for the short term (2009-2012) and medium term (2013-2017). In the study we consider the impact of the railway construction at two levels: the subregional (rayon) level and the regional (oblast) level. Our study finds that the infrastructure project had a statistically significant and positive impact on economic sectors, such as construction, agriculture, and industry, in the subregions under study compared to the control group. Furthermore, the results of the regional model showed that the construction of the railway has a statistically significant and economically growing impact on the tax revenues and regional GDP of the considered region. We found a more statistically significant impact on the increase in regional GDP of the region under study in the medium term by 18% of the mean regional GDP due to the railway construction. We also found a statistically significant and economically growing impact on tax revenues, increasing by 24% of the average taxes in the short term and by 42% in the medium term. Our study finds that the influence of the railway on macroeconomic indicators of the region under study has increased since its construction and in recent years has achieved a greater effect. In general, our study shows that the spillover effects of the project are significantly important for the local economy and can stimulate economic activity at the subregional and regional levels.
Keywords: L33; E6; H54; O22; R42; 330; public-private partnership; PPP; investment assessment; infrastructure project; econometric model; difference-in-difference method; DiD model; macroeconomic analysis